2021
DOI: 10.1088/1674-4527/21/10/268
|View full text |Cite
|
Sign up to set email alerts
|

Research on performances of back-illuminated scientific CMOS for astronomical observations

Abstract: To evaluate performances of a back-illuminated scientific CMOS (sCMOS) camera for astronomical observations, comparison tests between Andor Marana sCMOS and Andor iKon-L 936 CCD cameras were conducted in a laboratory and on a telescope. The laboratory tests showed that the readout noise of the sCMOS camera is about half lower, the dark current is about 17 times higher, the dynamic range is lower in the 12-bit setting and higher in the 16-bit setting, and the linearity and bias stability are comparable relative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…This, along with a limited QE due to being front-illuminated and a lower fill factor (Qiu et al 2013), do not make this sensor the most suitable for regular observations and its usefulness is mostly constrained to bright objects and high frame rates. The back-illuminated GSENSE2020 sensor, integrated in the Andor Marana, was recently tested for its application in astronomy by Qiu et al (2021) and Karpov et al (2021). It also showed a low readout noise (1.6 e − ), good linearity (99.7%) and a stable bias.…”
Section: Introductionmentioning
confidence: 99%
“…This, along with a limited QE due to being front-illuminated and a lower fill factor (Qiu et al 2013), do not make this sensor the most suitable for regular observations and its usefulness is mostly constrained to bright objects and high frame rates. The back-illuminated GSENSE2020 sensor, integrated in the Andor Marana, was recently tested for its application in astronomy by Qiu et al (2021) and Karpov et al (2021). It also showed a low readout noise (1.6 e − ), good linearity (99.7%) and a stable bias.…”
Section: Introductionmentioning
confidence: 99%
“…Camera displacement variation is one of the most important factors influencing the accuracy and stability of astronomical surveys [7]. This paper takes the Andor_iKON_L_936 camera [8] as the research object, analyses the micro-displacement produced by the camera due to the vibration that exists in its working process, and compares and verifies the experimental results, and finds that the change in the camera displacement in the water-cooled mode is significantly smaller than that in the air-cooled mode. The effect of camera displacement on optical imaging is analyzed, and a corresponding correction scheme is proposed to improve the stability of the camera.…”
Section: Introductionmentioning
confidence: 95%
“…In fact, there are also differences in performance between different brands of CMOS. A considerable amount of testing has been done on CMOS (Karpov et al 2020;Qiu et al 2021;Alarcon et al 2023), which has revealed the following unique problems such as the salt and pepper noise that are not seen with CCDs. However, these tests are solely on performance, and the astronomical tests of CMOS, such as photometric accuracy and extinction coefficient, are rare.…”
Section: Introductionmentioning
confidence: 99%